Pengaruh Penggunaan Media Kartu Angka Terhadap Kemampuan Berhitung Permulaan Anak Usia 5-6 Tahun - Widi Astuti, Ayu; Syafrudin, Ulwan; Oktaria, Renti (UIR PRESS, 2023)
The purpose of this study was to determine the effect of using number card media on the initial numeracy skills of children aged 5-6 years at Nur Ikhsan Kindergarten, Fajar Baru Village, Jati Agung, South Lampung. This type of research is quantitative with an experimental method with a one group pretest-posttest design. The sampling technique uses total sampling. The instruments used are observation and documentation sheets. The statistical analysis used was the Wilcoxon Signed Ranks Test. Of the 26 children who were studied in learning activities before using number card media, 0% were children in the high category and 42.30% were in the medium category, the remaining 57.7% were in the low category. Whereas in learning activities after using number card media, 42.30% of children were in the high category and 57.7% were in the medium category, the remaining 0% were in the low category. The results of the analysis show that there is a positive effect on the use of number card media on the initial numeracy skills of children aged 5-6 years, with an Asymp.Sign value of 0.000 <0.05. The significance value is less than 0.05, so the hypothesis is accepted. It is hoped that using media that is carried out routinely can improve the ability to recognize children's initial numeracy for the next.